Medicine, Health and Social Welfare in Post-1949 China - Bu, Liping; Fang, Xiaoping (Asian Studies E-Books Online, Collection 2025., 2025)
This volume features sixteen articles translated from the Chinese journal Historical Studies of Contemporary China (Dangdai zhongguo shi yanjiu). It covers a wide range of studies on policies and programs crucial to the health and welfare of the people during the PRC's social transformation. Topics include rural social security, the Five-Guarantee Program, disaster relief, food security, anti-drug campaigns, unity of Chinese and Western medicines, family planning, and senior homecare services. Using archival sources, these studies highlight key issues shaping health and well-being, inviting scholars and policy-makers to engage in discussions on these critical topics.